Commercialization of Sarawakian’s local product to broaden their market beyond the state - Abdul Rahman, Muhammad Asif; Amran, Muhammad Fadhli (2016)
Commercializing the Sarawak’s local product contributes to the profitable business. This study examines on problem faced by the local entrepreneurs in Sarawak who manufactured the food and beverages products, what are the major factors which contributes to the problem occurred, what kind ofstrategies that the local entrepreneurs in Sarawak recently implement and what are the best recommendations in order to curb all dissatisfaction faced by them. A random sample of 31 respondents which are among the members of Koperasi Persatuan Konsortium Groombig Sarawak Berhad (KOPKOS). Study shows they facing difficulties on the opportunity to promote their product globally which need several implement. Recognition of organization, their experience and knowledge and also the government’s assistance which are the major factors to the problem occurred. Most of them are using social media to promote their product besides their recommendation for the government are government should provide booths, site and seminar, minimizing the terms and regulation for application and conducting Research and Development (R&D).